Use of a Flexible Inflatable Multi-Channel Applicator for Vaginal Brachytherapy in the Management of Gynecologic Cancer - Shin, Samuel M.; Duckworth, Tamara L.; Cooper, Benjamin T.; Curtin, John P.; Schiff, Peter B.; DeWyngaert, J. Keith; Lymberis, Stella C. (Frontiers in oncology, 2015)
Evaluate use of novel multi-channel applicator (MC) Capri™ to improve vaginal disease coverage achievable by single-channel applicator (SC) and comparable to Syed plan simulation. Twenty-eight plans were evaluated from four patients with primary or recurrent gynecologic cancer in the vagina. Each received whole pelvis radiation, followed by three weekly treatments using HDR brachytherapy with a 13-channel MC. Upper vagina was treated to 5 mm depth to 1500 cGy/3 fractions with a simultaneous integrated boost totaling 2100 cGy/3 fractions to tumor. Modeling of SC and Syed plans was performed using MC scans for each patient. Dosimetry for MC and SC plans was evaluated for PTV700 cGy coverage, maximum dose to 2 cm(3) to bladder, rectum, as well as mucosal surface points. Dosimetry for Syed plans was calculated for PTV700 cGy coverage. Patients were followed for treatment response and toxicity. Dosimetric analysis between MC and SC plans demonstrated increased tumor coverage (PTV700 cGy), with decreased rectal, bladder, and contralateral vaginal mucosa dose in favor of MC. These differences were significant (p < 0.05). Comparison of MC and Syed plans demonstrated increased tumor coverage in favor of Syed plans which were not significant (p = 0.71). Patients treated with MC had no cancer recurrence or ≥grade 3 toxicity. Use of MC was efficacious and safe, providing superior coverage of tumor volumes ≤1 cm depth compared to SC and comparable to Syed implant. MC avoids excess dose to surrounding organs compared to SC, and potentially less morbidity than Syed implants. For tumors extending ≤1 cm depth, use of MC represents an alternative to an interstitial implant.